Robert E. Lee, brave leader - Bains, Rae.; Smolinski, Dick (Mahwah, NJ : Troll Associates, 1986)
Traces the life of the highly respected Confederate general, with an emphasis on his difficult boyhood in Virginia.
School Library Journal
5.0
3-6
Keywords: Lee, Robert E. -- 1807-1870 -- Juvenile literature; Lee, Robert E. -- 1807-1870.; United States. -- Army -- Biography -- Juvenile literature; Generals -- United States -- Biography -- Juvenile literature; Generals; Lee, Robert E., -- 1807-1870.; Generals